2017
DOI: 10.1097/qai.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Informing Strategies to Build PrEP Capacity Among San Francisco Bay Area Clinicians

Abstract: A large pool of clinicians is needed to meet growing demand for HIV pre-exposure prophylaxis (PrEP). We surveyed a mixed group of HIV specialists and non-specialists in the San Francisco Bay Area to determine their attitudes toward and training needs regarding prescribing PrEP to persons at increased risk of HIV infection. Willingness to prescribe was associated with experience in caring for HIV-infected patients (AOR 4.76, 95% CI 1.43-15.76, p=0.01). Desire for further training was associated with concerns ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…Results from this study demonstrate that pharmacy students were highly aware of PrEP and reported relatively high familiarity with prescribing guidelines. The high level of awareness is consistent with previous studies of HIV specialists and primary care providers 12,16,17,28,29 yet higher than in other studies of pharmacists 23 and medical providers. 19,30 A key finding in the analysis pertains to the connection between reported familiarity with PrEP prescribing guidelines and knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Results from this study demonstrate that pharmacy students were highly aware of PrEP and reported relatively high familiarity with prescribing guidelines. The high level of awareness is consistent with previous studies of HIV specialists and primary care providers 12,16,17,28,29 yet higher than in other studies of pharmacists 23 and medical providers. 19,30 A key finding in the analysis pertains to the connection between reported familiarity with PrEP prescribing guidelines and knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Suggestions from the contraceptive and oral PrEP studies on how to overcome these issues may be helpful. For instance, concerted efforts (eg, trainings) to ensure that providers have accurate information about PrEP [ 37 , 38 ] implants (including information on insertion and removal techniques) and effective tools to identify PrEP implant candidates could be helpful. Same-day access to PrEP implant insertion could also boost uptake [ 39 ]; offering PrEP implants in emergency department settings could also boost implant uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Although PrEP is widely recognized as an efficacious HIV prevention tool, it is not commonly prescribed. Studies examining the adoption of PrEP offer limited insight on the role of APNs concerning PrEP (Bacon et al, 2017;Hakre et al, 2016;Mullins et al, 2015). This…”
Section: Pre-exposure Prophylaxis Risk Evaluation and Mitigationmentioning
confidence: 99%
“…Barriers to PrEP referral and prescription include a general lack of knowledge about PrEP, difficulty in identifying individuals most likely to benefit from a PrEP intervention and disagreement about the optimal healthcare settings to prescribe PrEP (Bacon et al, 2017;Karris, Beekmann, Mehta, Anderson, & Polgreen, 2014;Krakower, Ware, Mitty, Maloney, & Mayer, 2014). Some healthcare providers suggest an HIV specialist care setting is the optimal venue to prescribe PrEP because those practitioners understand the care of people living with HIV and are most comfortable with the required longitudinal patient motoring.…”
Section: Introductionmentioning
confidence: 99%